Komparasi Hukum Islam dan Hukum Perdata Terhadap Ganti Kelamin dan Konsekuensi Yuridisnya - Dian Saputra; Karimuddin Abdullah Lawang (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
Genital replacement is an interesting issue to be studied today. Especially with regard to the impact on civil rights after sex surgery is carried out. This study aims to comprehensively analyze the practice of sex change in the perspective of legislation and Islamic law and the juridical consequences of this sex change. The research method used is a normative juridical research method using data from library literature. In addition, researchers also use primary legal materials contained in the Civil Code and the Marriage Law. Data analysis was carried out qualitatively. The results of the study indicate that normatively the practice of sex change is allowed for reasons of benefit, whereas if the motivation is for other interests, Islamic teachings forbid it. The juridical consequences after sex change can occur in the aspect of marriage and the distribution of inheritance, because the Marriage Law only recognizes marriage between a man and a woman. The distribution of inheritance for people who change their genitals must be done carefully by taking into account their gender, both male and female.